Integrative Strategies for Preventing Nutritional Problems in the Development of Children in Brazil - Fisberg, Mauro; Duarte Batista, Lais; Nogueira-de-Almeida, Carlos Alberto; Sarti, Flávia Mori; Albuquerque, Maria Paula de; Fisberg, Regina Mara (Frontiers in Nutrition, 2021)
Child health care has been a priority subject in several programs and public policies developed over the decades. However, initiatives implemented seem insufficient to overcome the challenges regarding integral development and improvement of children’s nutritional status in Brazil. The child’s initial development stages include pregnancy, breastfeeding, and complementary feeding, which are determinants in future aspects of health and nutritional status. Therefore, strategies addressing problems during these three periods of life have the potential to positively impact the promotion of healthy eating habits and food security throughout life. Developing countries with huge dimensions and vast inequalities, like Brazil, are marked by differences in regional, cultural, and social contexts that may hinder the implementation of programs and policies with a broad scope. Extensive operational and professional costs, in addition to time-consuming activities necessary to application, monitor, and evaluate interventions may jeopardize the proper assessment of programs and policy goals, generating inefficiency and waste of resources in the health system. Thus, programs and policies aimed at creating and modifying habits should consider an intersectoral action within local contexts, involving health professionals, universities, policy managers, and the community. Therefore, this paper aimed to discuss the preliminary conception of an integrated approach of decentralized strategies to promote healthy eating habits and food security of children in Brazil.